SPE Annual Technical Conference and Exhibition 1987
DOI: 10.2118/16763-ms
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Model for Composite Reservoirs Produced at Either Constant Bottomhole Pressure or Constant Rate

Abstract: In this paper, we present a model of the complete characteristic transient response from a composite reservoir including the effects of skin, wellbore storage and phase redistribution at the well. We present six flow regimes and the combined effects of wellbore storage and phase redistribution on pressure behavior in composite reservoirs.Using an automatic history matching approach, we analyzed three buildup tests and a pressure falloff test.This method eliminated the serious uniqueness problem associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…As discussed above, the Barenblatt et al (1960) and Warren and Root (1963) type models have been used (Camacho-Velazquez et al, 2008;Da Prat et al, 1981;Ozkan et al, 1987;Raghavan and Ohaeri, 1981;Sageev et al, 1985) for rate transient and decline curve analyses. In earlier papers Kuchuk andBiryukov, 2013, 2014), we showed that the Barenblatt et al (1960) and Warren and Root (1963) type models are inappropriate and incomplete for naturally fractured reservoirs.…”
Section: Mathematical Model For Rate Transient Analysis In Fractured mentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed above, the Barenblatt et al (1960) and Warren and Root (1963) type models have been used (Camacho-Velazquez et al, 2008;Da Prat et al, 1981;Ozkan et al, 1987;Raghavan and Ohaeri, 1981;Sageev et al, 1985) for rate transient and decline curve analyses. In earlier papers Kuchuk andBiryukov, 2013, 2014), we showed that the Barenblatt et al (1960) and Warren and Root (1963) type models are inappropriate and incomplete for naturally fractured reservoirs.…”
Section: Mathematical Model For Rate Transient Analysis In Fractured mentioning
confidence: 99%
“…A number of papers have been published on the rate transient behavior of naturally fractured (also called two-porosity, double-porosity, dual-porosity, or fissured) reservoirs using Barenblatt et al (1960) and Warren and Root (1963) type models (Camacho-Velazquez et al, 2008;Da Prat et al, 1981;Ozkan et al, 1987;Raghavan and Ohaeri, 1981;Sageev et al, 1985). A few papers are published on the rate transient behavior of triple-porosity (three-porosity) naturally fractured reservoirs (Al-Ahmadi and Wattenbarger, 2011;Ezulike and Dehghanpour, 2013;Tivayanonda et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Olarewaju, J.S. and Yu, J.P. et al completed a series of studies in the composite reservoir model with different types of applications [6][7] . Chu, L. and Yin Hongjun et al studied the pressure transient analysis of production well and injection well in triple and multiple composite reservoir [8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Other investigations regarding the composite resevroir model with different types of applications were conducted, such as the effect of phase segragation, mobility contrast and conductivity ratio. Some researchers have mentioned the potential applications of reservoirs with a fluid bank and a burning front [2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%